Guidelines' risk assessment recommendations for venous thromboembolism prophylaxis: A comparison and implementability appraisal. Issue 168 (August 2018) - Moesker, M.J.; Damen, N.L.; Volmeijer, E.E.; Dreesens, D.; de Loos, E.M.; Vink, R.; Coppens, M.; Kruip, M.J.; Meijer, K.; Langelaan, M.; de Bruijne, M.C.; Wagner, C.
Abstract: Introduction: Venous thromboembolism (VTE) prophylaxis guidelines for non-surgical patients recommend VTE- and bleeding risk assessment to guide prophylactic strategies. These recommendations differ between guidelines and implementation is suboptimal. Assessing a guideline's implementability characteristics helps predicting the ease of implementation and reveals barriers. Objectives: We aimed to compare guidelines' risk assessment recommendations and critically appraise the implementability characteristics. Material and methods: Two guidelines, one from the American College of Chest Physicians and one from the National Institute for Health and Care Excellence were selected for comparison. Risk assessment methods and subsequent prophylactic recommendations were compared. Eight experts then appraised the guideline recommendations on intrinsic implementability characteristics using the GuideLine Implementability Appraisal (GLIA) instrument. GLIA identifies barriers and facilitators for guideline implementation in nine dimensions. Results: Eleven out of 20 individual VTE-risk factors and 2 out of 19 individual bleeding-risk factors used, were present in both guidelines. Additionally, a high VTE- or bleeding risk was defined differently between the two guidelines. The GLIA appraisal identified implementation barriers within all recommendations analyzed. On content level, barriers were identified in recommendations addressing bleeding risk assessment, mechanical prophylaxis and critical care patients. On implementability level, barriers were identified in decidability, flexibility, effect on process of care and computability dimensions. Conclusion: Depending on the guideline used, VTE-prophylaxis will most likely be provided to different non-surgical patient populations, primarily due to discordance in bleeding risk assessment. Revising the recommendations, taking into account the most apparent implementation barriers, should be considered. However, insufficient evidence to support the recommendations currently complicates this. Highlights: Implementation of VTE prophylaxis guidelines for non-surgical patients is known to be suboptimal. We compared VTE prophylaxis risk assessment recommendations and appraised their implementability characteristics. We found differences in risk assessment recommendations, especially within bleeding risk assessment. We found implementation barriers concerning bleeding risk, mechanical prophylaxis and critical care patients. The implementation barriers should be taken into account when revising VTE prophylaxis guidelines.